Perinatal outcomes in lesbian couples employing shared motherhood IVF compared with those performing artificial insemination with donor sperm. Issue 5 (3rd April 2023) - Matorras, R; Perez-Fernandez, S; Hubel, A; Ferrando, M; Quintana, F; Vendrell, A; Hernandez, M
Abstract: STUDY QUESTION: In lesbian couples, is shared motherhood IVF (SMI) associated with an increase in perinatal complications compared with artificial insemination with donor sperm (AID)? SUMMARY ANSWER: Singleton pregnancies in SMI and AID had very similar outcomes, except for a non-significant increase in the rate of preeclampsia/hypertension (PE/HT) in SMI (recipient's age-adjusted odds ratio (OR) = 1.9, 95% CI = 0.7–5.2; P = 0.19), but twin SMI pregnancies had a much higher frequency of PE/HT than AID twins (recipient's age-adjusted OR = 21.7, 95% CI = 2.8–289.4; P = 0.01). WHAT IS KNOWN ALREADY: Oocyte donation (OD) pregnancies are associated with an increase in perinatal complications, in particular, preterm delivery and low birth weight, and PE/HT. However, it is unclear to what extent these complications are due to OD process or to the conditions why OD was performed, such as advanced age and underlying health conditions. Unfortunately, the literature concerning perinatal outcomes in SMI is scarce. STUDY DESIGN, SIZE, DURATION: Retrospective study involving 660 SMI cycles (299 pregnancies) and 4349 AID cycles (949 pregnancies) assisted over a 10-year period. PARTICIPANTS/MATERIALS, SETTING, METHODS: All cycles fulfilling the inclusion criteria performed in lesbian couples seeking fertility treatment in 17 Spanish clinics of the same group. Pregnancy rates of SMI and AID cycles were compared. Perinatal outcomes were compared: gestational length, newborn weight, preterm and low birth rates, PE/HT rates, cesarean section rates, perinatal mortality, and newborn malformations. MAIN RESULTS AND THE ROLE OF CHANCE: Pregnancy rates were higher in SMI than in AID (45.3% versus 21.8%, P < 0.001). There was a non-significant trend to higher multiple rate in AID (4.7% versus 8.5%, P = 0.08). In single pregnancies, there were no differences between SMI and AID in gestational age (278 days (268–285) versus 279 (272–284), P = 0.24), preterm rate (8.3% versus 7.3%, P = 0.80), preterm <28 weeks (0.6% versus 0.4%, P = 1.00), newborn weight (3195 g (2915–3620) versus 3270 g (2980–3600), P = 0.296), low birth rate (6.4% versus 6.4%, P = 1.00), extremely low birth weight (0.6% versus 0.5%, P = 1.00), and the distribution of newborns by weight groups. Cesarean section rate, newborn malformation rate, and perinatal mortality were also similar in SMI and AID. Additionally, there was non-significant trend in hypertensive disorders to an increase in PE/HT among SMI (recipient's age-adjusted OR = 1.9, 95% CI = 0.7–5.2). Overall, perinatal data are consistent with what is reported in the general population. In twin pregnancies, the aforementioned perinatal parameters were also very similar in SMI and AID. However, SMI twin pregnancies had a very high risk of PE/HT when compared with AID (recipient's age-adjusted OR = 21.7, 95% CI = 2.8–289.4, P = 0.01). LIMITATIONS, REASONS FOR CAUTION: Our data regarding the pregnancy course were obtained from information registered in the delivery report as well as from what was reported by the patients themselves, so a certain degree of inaccuracy cannot be ruled out. Additionally, in some parameters, there was up to 10% of data missing. However, since the methodology of reporting was the same in SMI and AID groups, one should not expect a differential reporting bias. It cannot be ruled out that the risk of PE/HT in simple gestations would be significant in a larger study. Additionally, in the SMI group allocation to the transfer of 2 embryos was not randomized so some bias is possible. WIDER IMPLICATIONS OF THE FINDINGS: SMI, if single embryo transfer is performed, seems to be is a safe procedure. Double embryo transfer should not be performed in SMI. Our data suggest that the majority of complications in OD could be related more with recipient status than with OD itself, since with SMI (performed in women without fertility problems) the perinatal complications were much lower than usually described in OD. STUDY FUNDING/COMPETING INTEREST(S): No external funding was received. The authors declare that they have no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.